Implementation of Islamic Business Ethics Values based on IFSB 09: BMT La Tansa Ponorogo Experience - Ely Windarti Hastuti; Fajar Surya Ari Anggara (Al Tijarah, 2017)
The importance of ethics in the business world is of high priority and global importance. New trends and problems arise every day which is a major challenge for any organization. Today, the need for ethical behavior in organizations has become important. Just as, if a dishonest business practice, only thinking about the maximum profit and harming the other will bring an institution will no longer be trusted and gradually lost. So the purpose of this research is the implementation of Islamic business ethics based on IFSB standard 09. It is proven from the overall result of interview analysis, observation, and transcript of interview result. BMT La Tansa Ponorogo has a series of activities within the scope of strengthening and cultivation of values that serve as the foundation of all operational activities. These values include Sincerity, Simplicity, Independence, Islamic Prayer, and Freedom. In conducting business and activities, business actors have understood and implemented Islamic principles or values based on Al Qur’an and Hadith. Implementation of this Islamic business ethics that includes aspects of honesty and fairness, prudential aspects, aspects of ability, information aspects for customers, aspects of information about customers, solutive aspects of conflict of interest, and aspects of Shari’a compliance.